2022
DOI: 10.1249/mss.0000000000002861
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Perceptual, and Performance Responses to the 2-Week Block of High- versus Low-Intensity Endurance Training

Abstract: Purpose: This study examined the physiological, perceptual, and performance responses to a 2week block of increased training load and compared whether responses differ between highintensity interval (HIIT) and low-intensity (LIT) endurance training. Methods: Thirty recreationally trained males and females performed a two-week block of 10 HIIT-sessions (INT, n = 15) or 70 % increased volume of LIT (VOL, n = 15). Running time in the 3000 m and basal serum and urine hormone concentrations were measured before (T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Despite the fact that this was confirmed "only" by estimated readiness to train, the marker has been useful in the prediction of functional overreaching, 29 and has also been associated with the acute changes in performance followed by highintensity interval training block. 24 When evaluating current responses, changes of HR and HRV were greatest in magnitude in 4H and FULL segments, and the averages exceeded the typical error. Previously, the responses to endurance exercises in nocturnal recordings have been somewhat contradictory, as some have found greater increases in HR and decrements in HRV 16,19 compared with the present study, while others have found changes only in HR 15,20,21 despite late-time exercise.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite the fact that this was confirmed "only" by estimated readiness to train, the marker has been useful in the prediction of functional overreaching, 29 and has also been associated with the acute changes in performance followed by highintensity interval training block. 24 When evaluating current responses, changes of HR and HRV were greatest in magnitude in 4H and FULL segments, and the averages exceeded the typical error. Previously, the responses to endurance exercises in nocturnal recordings have been somewhat contradictory, as some have found greater increases in HR and decrements in HRV 16,19 compared with the present study, while others have found changes only in HR 15,20,21 despite late-time exercise.…”
Section: Discussionmentioning
confidence: 90%
“…Recreational male and female runners were recruited for a larger study project, 24 during which the current data collection was executed. Subjects whose full nocturnal HR and HRV data were available after the 2 first consecutive LIT sessions of the training period (n = 15) and/ or the night before and after the second 3000-m test of the study (n = 23) were involved in the analysis.…”
Section: Subjectsmentioning
confidence: 99%
“…During INT, the weekly main session was 6 × 3 min performed at the maximal sustainable effort with 2-min recovery intervals in between ( 27 ). Basically, the running speed during the intervals was between the second lactate threshold and maximal treadmill test speed and at the end of intervals, HR reached values above the second lactate threshold (HRzone3).…”
Section: Methodsmentioning
confidence: 99%
“…Fatigue was expected to be sensitive for the (too high) changes in the training load ( 22 , 23 ) and to increase as a sign of possible overreaching ( 30 , 31 ). Muscle soreness has also increased after periods of intensified training ( 23 , 27 , 32 ), and high values may relate to overtraining ( 30 ). Hooper et al ( 30 ) suggested that in a 1–7 scale, values >5 would be associated with staleness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation